Numerical validation of a synthetic cell-based model of blood coagulation. (7th September 2015) - Pavlova, J.; Fasano, A.; Janela, J.; Sequeira, A.
Abstract: In Fasano et al. (2012) a new reduced mathematical model for blood coagulation was proposed, incorporating biochemical and mechanical actions of blood flow and including platelets activity. The model was characterized by a considerable simplification of the differential system associated to the biochemical network and it incorporated the role of blood slip at the vessel wall as an extra source of activated platelets. The purpose of this work is to check the validity of the reduced mathematical model, using as a benchmark the model presented in Anand et al. (2008), and to investigate the importance of the blood slip velocity in the blood coagulation process. Abstract : Highlights: A simplified mathematical model for blood coagulation is considered including blood slip. Numerical simulations have been performed in a 2-D geometry. The same results have been obtained as models of higher complexity with no blood slip. The influence of blood slip has been emphasized. Advantages and limitation of the model have been illustrated.